ENEM na Rede: a social, online and free environment to support Brazilian students in knowledge creation - Arrais, Marcos; Oliveira, Jonice (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
This paper presents the structure and functionalities of the “ENEM na Rede” tool, a free online platform that helps students from Brazil in preparing for the National High School Exam (Exame Nacional do Ensino Médio – ENEM). The application uses social networking and gamification concepts to build an engaging environment conducive to knowledge building. During the use of the platform students are introduced to the exam content through an automated method that detects deficiencies and proficiency in the exam areas.